2011
DOI: 10.3346/jkms.2011.26.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Necrotizing Fasciitis Due toStreptococcus pneumoniae: A Case Report

Abstract: Necrotizing fasciitis is known to be a highly lethal infection of deep-seated subcutaneous tissue and superficial fascia. Reports of necrotizing fasciitis due to Streptococcus pneumoniae are exceedingly rare. We report a case of necrotizing fasciitis in a 62-yr-old man with liver cirrhosis and diabetes mellitus. He presented with painful swelling of left leg and right hand. On the day of admission, compartment syndrome was aggravated and the patient underwent surgical exploration. Intra-operative findings reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
5
0
5
Order By: Relevance
“…S. pneumoniae, which was dominant in samples from patient 8, is a widespread pathogen that displays enormous heterogeneity with respect to phenotype and pathogenicity, and has been implicated in community-acquired pneumonia, sinusitis, otitis media, orthopaedic infections and meningitis [44, 6062]. NSTI due to S. pneumoniae is rare and has primarily been reported in cases where patients were immunosuppressed or had other underlying conditions [21, 6367], which does not correspond to the patient history in this case (Table 1). However, serious infections upon septic spread of the S. pneumoniae including to joints and bursas, as in this case, is not unusual.…”
Section: Discussionmentioning
confidence: 99%
“…S. pneumoniae, which was dominant in samples from patient 8, is a widespread pathogen that displays enormous heterogeneity with respect to phenotype and pathogenicity, and has been implicated in community-acquired pneumonia, sinusitis, otitis media, orthopaedic infections and meningitis [44, 6062]. NSTI due to S. pneumoniae is rare and has primarily been reported in cases where patients were immunosuppressed or had other underlying conditions [21, 6367], which does not correspond to the patient history in this case (Table 1). However, serious infections upon septic spread of the S. pneumoniae including to joints and bursas, as in this case, is not unusual.…”
Section: Discussionmentioning
confidence: 99%
“…7 Various predisposing factors are described for the development of necrotizing fasciitis such as rheumatoid arthritis, SLE, diabetes, post renal transplantation, injection drug abusers, obesity, malnutrition, anaemia, immunocompromised patients or on immunosuppressive therapy. 8,9 Post-operative infections accounts for 20%, and it usually follows trivial trauma. In this case, anaemia, low serum protein, poor nourishment, and improper hygiene were found to be predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing fasciitis due to Streptococcus pneumoniae is extremely rare, with only 20 cases reported in the English literature by April 2014, of which 11 patients died despite extensive surgical debridement and broad-spectrum antibiotic treatment [ 5 ]. Previously reported predisposing factors included rheumatoid arthritis, SLE, type 2 diabetes mellitus, renal transplantation, injection drug use, immunosuppressive therapy, and intramuscular injection with nonsteroidal anti-inflammatory drugs [ 1 , 5 ]. Here, we report a case of early diagnosed necrotizing fasciitis due to Streptococcus pneumoniae in a 26-year-old gentleman who was immune-compromised with prednisone/cyclophosphamide treatment for his severe connective tissue disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 22 patients with necrotizing fasciitis, 59% were found to only have erythematous and tender skin lesions on day 0, whereas signs more suggestive of necrotizing fasciitis such as crepitus and frank necrosis occurred in fewer than 5% of patients on day 0, and in 68% by day 4 [ 12 ]. Pain out of proportion to the physical findings was considered to be the most consistent finding in the early stage, which was found in 98% of patients with necrotizing fasciitis on admission [ 5 ]. The clinical manifestations of our patient agreed with the first stage of necrotizing fasciitis proposed in the aforementioned study, characterized by relatively stable vital signs, rapidly developing intense erythema, and disproportionate pain [ 12 ].…”
Section: Discussionmentioning
confidence: 99%